Three-year assessment of cadmium exposure and bone mineral density changes in cadmium-contaminated areas in northwestern Thailand - Aroon La-up; Udomsak Saengow; Tawisa Umpong; Phuwasin Buakate; Mondhakarn Oprasertsawat (PLoS ONE, 2025)
Chronic cadmium exposure is linked to bone loss, but its effect on the short-term progression of bone mineral density (BMD) in previously exposed populations is not well understood. This study aimed to investigate the association between baseline urinary cadmium (U-Cd) levels and the subsequent three-year change in BMD in a chronically exposed cohort in northwestern Thailand. We conducted a three-year longitudinal study of 393 residents (40 men, 353 women) aged 35 and older. Baseline (2019) U-Cd was the primary exposure, and BMD at the calcaneus was measured in 2019 and 2022. Dual-energy X-ray absorptiometry was used for BMD measurements and atomic absorption spectrometry for U-Cd analysis. The mean U-Cd levels in males (7.18 ± 1.35 μg/g creatinine) were significantly higher (p < 0.001) than in females (3.68 ± 2.13 μg/g creatinine). This study found a statistically significant decrease in BMD in the group with the lowest U-Cd levels (<2.0 μg/g creatinine, p = 0.001) and in the overall sample (from 0.392 ± 0.079 μg/g creatinine in 2019 to 0.384 ± 0.094 μg/g creatinine in 2022, p = 0.004). However, no statistically significant changes were observed in groups with U-Cd levels above 2.0 μg/g creatinine. Osteoporosis prevalence remained stable in both males and females. The Linear Mixed-Effects Model analysis revealed significant associations between BMD and several factors: increasing age, female sex, diabetes status and BMI. Age and female sex were negatively associated with BMD, while BMI showed a positive relationship. U-Cd levels were not significantly associated with BMD changes over the three-year period (coefficient = −0.002, p = 0.073), though a slight downward trend in BMD was observed across all cadmium exposure levels. This study underscores the complexity of cadmium’s effects on bone health and emphasizes the need for longer-term follow-up studies to better understand the potential cumulative impact of cadmium exposure on BMD.